Pazopanib-Induced Alopecia, an Underestimated Toxicity? - Biondo, Andrea; Alexander, Helen; Khabra, Komel; Pickering, Lisa; Gore, Martin; Larkin, James (Frontiers in Oncology, 2015)
Pazopanib and sunitinib are treatment options for metastatic renal cell cancer (mRCC), with similar efficacy, and minor differences in their toxicity profile. Our experience has suggested that pazopanib-induced alopecia may be a potentially significant but previously under-reported toxicity. For this reason, we performed a retrospective review of the clinical records of all patients with mRCC treated with pazopanib at the Royal Marsden Hospital from European licensing until June 2013, and all patients treated with sunitinib over the same period. We found that 36 patients with mRCC were treated with pazopanib and 85 patients with sunitinib. Four of the 36 (11%) patients treated with pazopanib developed alopecia severe enough to warrant a wig versus none of 85 patients treated with sunitinib (p = 0.007). In conclusion, grade 2 pazopanib-induced alopecia was reported at significantly higher rates when compared to sunitinib-induced alopecia. Hence, in our view, patients should be informed about this potential toxicity when discussing the treatment options for mRCC.